Rare Earth Doped Lanthanum Calcium Borate Polycrystalline Red Phosphors. (5th August 2014) - Xiong, H. H.; Zhu, C.; Zhao, X.; Wang, Z. Q.; Lin, H.
Abstract : Single-phased Sm 3+ doped lanthanum calcium borate (Sm x La2− x CaB10 O19, SLCB, x = 0.06 ) polycrystalline red phosphor was prepared by solid-state reaction method. The phosphor has two main excitation peaks located at 398.5 nm and 469.0 nm, which are nicely in accordance with the emitting wavelengths of commercial near-UV and blue light emitting diode chips. Under the excitation of 398.0 nm, the dominant red emission of Sm 3+ in SLCB phosphor is centered at 598.0 nm corresponding to the transition of 4 G5/2 → 6 H7/2 . The Eu 3+ fluorescence in the red spectral region is applied as a spectroscopic probe to reveal the local site symmetry in the host lattice and, hence, Judd-Ofelt parameters Ω t ( t = 2, 4 ) of Eu 3+ in the phosphor matrix are derived to be 3.62 × 10 -20 and 1.97 × 10 -20 cm 2, indicating a high asymmetrical and strong covalent environment around rare earth luminescence centers. Herein, the red phosphors are promising good candidates employed in white light emitting diodes (LEDs) illumination.